Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1136/bmj.308.6941.1411
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding and multiple sclerosis

Abstract: cervical canal and from around the external os is paramount.29 The correlation between cytology and histologyboth of which are subjective-leaves much to be desired,"03' yet smear surveillance has worked well to date. Women who have even one abnormal smear'2 are at greater risk of having some grade of cervical intraepithelial neoplasia than women who have normal smears. They require rigorous smear surveillance, which will allow at least one third of patients to return to normal and avoid unnecessary treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 5 publications
1
26
1
Order By: Relevance
“…Greater understanding of fetal development and early maternal influences on the fetus and child is needed. A multitude of early risk factors could potentially be involved, for example, the length of breast feeding has been associated with susceptibility to MS [22] . Studies recording information on such developmental influences are required before the early origins of MS can be assessed to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Greater understanding of fetal development and early maternal influences on the fetus and child is needed. A multitude of early risk factors could potentially be involved, for example, the length of breast feeding has been associated with susceptibility to MS [22] . Studies recording information on such developmental influences are required before the early origins of MS can be assessed to a greater extent.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies investigated the role of breastfeeding on the incidence of MS, but results of the studies were not conclusive (14,15).…”
Section: Diet As a Cause Of Msmentioning
confidence: 99%
“…While 14 It is well established that pre-term and full-term infants fed on formula feeds have lower plasma and erythrocyte levels of DHA and AA than breastfed infants. 15,16 Several studies [17][18][19] have shown a correlation between infant feeding and the development of neuropsychiatric disorders. There is further, growing evidence that functional neurodevelopment is abnormal in infants and children who later develop schizophrenia.…”
Section: Discussionmentioning
confidence: 99%